2014
DOI: 10.1016/j.bbmt.2014.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Human Factor VIIa for Alveolar Hemorrhage Following Allogeneic Stem Cell Transplantation

Abstract: The mortality rate of alveolar hemorrhage following allogeneic hematopoietic stem cell transplantation is greater than 60% with supportive care and high dose steroids. We performed a retrospective cohort analysis to assess the benefits and risks of rFVIIa as a therapeutic adjunct for alveolar hemorrhage. From 2005 to 2012, 57 episodes of alveolar hemorrhage occurred in 37 patients. Fourteen episodes (in 14 patients) were treated with steroids alone and 43 episodes (in 23 patients) were treated with steroids an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 45 publications
0
35
0
Order By: Relevance
“…24 Other agents such as recombinant factor VIIa have also been studied retrospectively, with a recent study suggesting no benefit. 7 ACA is an antifibrinolytic agent classically used intravenously to control perioperative bleeding, mainly in cardiac surgery. [28][29][30][31] To our knowledge, the only previous study of i.v.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Other agents such as recombinant factor VIIa have also been studied retrospectively, with a recent study suggesting no benefit. 7 ACA is an antifibrinolytic agent classically used intravenously to control perioperative bleeding, mainly in cardiac surgery. [28][29][30][31] To our knowledge, the only previous study of i.v.…”
Section: Discussionmentioning
confidence: 99%
“…5 It has been reported to affect~5-12% of HSCT patients yearly; however, more recent studies indicate the incidence to be closer to 5%. [6][7][8] BAL fluid, however, lacks sensitivity and specificity when compared with autopsy findings, which hinders early and accurate diagnoses. 9 Despite prompt therapy and supportive care, the mortality rate for DAH remains high at 60-100%.…”
Section: Introductionmentioning
confidence: 99%
“…DAH is generally seen in the first 30 days after allo-HSCT with the incidence of 2-14% and the mortality rates of over 60%. 62,63 DAH etiology is not elucidated in the context of transplantation. While infections, cardiac causes including heart failure, toxicity from pre-transplant thoracic radiation, chemotherapy and early marrow engraftment are the factors leading to DAH, no definite cause could be detected in 20% of patients.…”
Section: Diffuse Alveolar Hemorrhagementioning
confidence: 99%
“…Predictably, supportive therapy includes oxygen and ventilation support, transfusion of blood products and antimicrobial therapy. 62 Rathi NK et al classified the cases of post transplant DAH in three groups according to methylprednisolone doses in the treatment 66 : (1) low dose: < 250 mg/day, (2) medium dose: 250-1000 mg/day and (3) high dose: ≥ 1000 mg/day. Authors concluded that intensive care unit and hospital mortality significantly low only in low-dose steroid group and stated that treatment strategies may need to be reanalyzed in order to avoid potential unnecessary therapies.…”
Section: Diffuse Alveolar Hemorrhagementioning
confidence: 99%
“…6 In addition, aminocaproic acid and recombinant factor VIIa have been tried in some studies with variable results. 11 However, a recent report showed no difference in outcome with methylprednisolone at low doses (≤ 250 mg/d), medium doses (250-1000 mg/d), or high doses (≥ 1000 mg/d) with or without the addition of aminocaproic acid. 12 Mortality rates in patients with DAH range from 74% to 100%.…”
Section: Introductionmentioning
confidence: 96%